The incidence, mortality, and survival rate of colorectal cancer in Xiamen, China, from 2011 to 2020 - Lingxian Qiu; Wenting Luo; Youlan Chen; Zhinan Guo; Jiali Quan; Jiahuang Chi; Yingying Guan; Yue Huang; Yilan Lin (BMC Public Health)
Abstract Introduction Currently, nearly one-third of newly diagnosed Colorectal cancer (CRC) cases and associated deaths worldwide are from China. Among Chinese provinces, Fujian exhibited the highest CRC mortality rate. This study aims to analyze long-term trends of CRC epidemiology in Xiamen, Fujian, China. Methods Data were obtained from various cancer surveillance systems, including the Xiamen Cancer Register system, the Xiamen Death Register system, and the household registration system. Trends in incidence, mortality and survival rates from 2011 to 2020 were analyzed using annual percent changes (APC) and average annual percent changes (AAPC), stratified by sex and residency status. Results A total of 7,406 new cases and 3,726 CRC-related deaths were reported from Xiamen. The age-standardized of incidence and mortality rates were 26.09 per 100,000 and 12.70 per 100,000, respectively. The observed 5-year survival rate was 46.65%, with an age-standardized survival of 51.24%. CRC incidence in Xiamen is significantly increasing (AAPC = 4.90%). In contrast, trends in CRC mortality and survival rates are not significant. Urban areas exhibited higher rates of CRC incidence, mortality, and survival rate compared to rural areas, though rural areas showed a more marked upward trend. Conclusions The burden of CRC in Xiamen is notably high, with a concerning increasing in incidence. This underscores the urgent need for targeted strategies to address this public health challenges.